Istoriograficheskii analiz rekordov v plavanii - Volkov, N. I.; Popov, O. I. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this study - an analysis of the world records in swimming - was to substantiate the forecast of development in some kinds of the sports swimming. The equation of exponential function was used to analyse the curve of records' growth. The stages of the contemporary swimming development had been revealed. The "correlation" between the acceleration of records' dynamics and the periods of "methodical revolutions" had been discovered.